2020
DOI: 10.1101/2020.02.17.952374
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Vaccinia Virus Infection Inhibits Skin Dendritic Cell Migration to Draining Lymph Node

Abstract: 18 Despite the success of Vaccinia virus (VACV) against smallpox there remains a paucity of 19 information on Dendritic cell (DC) responses to the virus, especially on the traffic of DCs and 20 VACV to draining LN (dLN). Herein we studied skin DC migration in response to VACV and 21 compared it to the tuberculosis vaccine Mycobacterium bovis Bacille Calmette-Guérin (BCG), 22 another live-attenuated vaccine administered via the skin. In stark contrast to BCG, skin DCs 23 did not relocate to dLN in response to V… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…skin infection suggested that dendritic cell migration from the skin to draining lymph nodes is impaired on VACV 56 . The relocation of the virus from the skin to the lymphatics might also be supported by other mechanisms such as direct lymphatic vessel access, as observed in skin infection models of Zika virus 57 .…”
Section: ();mentioning
confidence: 99%
“…skin infection suggested that dendritic cell migration from the skin to draining lymph nodes is impaired on VACV 56 . The relocation of the virus from the skin to the lymphatics might also be supported by other mechanisms such as direct lymphatic vessel access, as observed in skin infection models of Zika virus 57 .…”
Section: ();mentioning
confidence: 99%
“…In addition to infecting tissue-resident antigen-presenting cells, including DCs, Langerhans cells, macrophages, and monocytes, viruses can also employ mobile antigen-presenting cells to spread via the lymphatic system (Norbury et al, 2002;Deng et al, 2008;Cann et al, 2013). Despite this, recent research using an orthopoxvirus-infected mouse skin model suggests that VACV impedes DCs immigration from the skin to lymph node drainage (Aggio et al, 2021). Direct access to lymphatic vessels, as seen in Zika virus cutaneous infection models, may also play a role in the virus's migration from the surface to the lymphatics (Reynoso et al, 2019).…”
Section: Immunopathogenesis Of Mpoxmentioning
confidence: 99%
“…Since numerous nascent viruses are wrapped inside the cell, VICM is a good choice for the virus to avoid immune system defense such as antibody neutralization. In addition, VACV infection can impair the migratory capacity of skin dendritic cells from the infection sites to draining lymph node 37 , which is also a potential way of immune escape for the vaccinia. Besides (which was not certified by peer review) is the author/funder.…”
Section: Discussionmentioning
confidence: 99%